2004
DOI: 10.1038/sj.bjc.6602183
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type oestrogen receptor beta (ERβ1) mRNA and protein expression in Tamoxifen-treated post-menopausal breast cancers

Abstract: This study has tested the hypothesis that comparison of protein and mRNA expression for ERa and ERb1 by human breast cancers provides novel information relating to the clinical and pathological characteristics of human breast cancers. Expression of ERa and ERb1 was identified in 167 invasive cancers from postmenopausal women treated only with endocrine therapy. The cohort included 143 cases receiving only adjuvant Tamoxifen following surgery. ERa and ERb1 expression was analysed by immunohistochemistry and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
2
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 26 publications
(55 reference statements)
9
100
2
4
Order By: Relevance
“…Moreover, loss of ERb was observed to be associated with tamoxifen resistance whereas increase of ERb expression in MCF-7 cells enhanced the antiproliferative and apoptotic effect of antiestrogens (HodgesGallagher et al, 2008). However, data regarding the association of ERb expression with clinical pathological parameters and antiestrogen responsiveness are still mixed (Speirs et al, 1999;O'Neill et al, 2004;Murphy and Watson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, loss of ERb was observed to be associated with tamoxifen resistance whereas increase of ERb expression in MCF-7 cells enhanced the antiproliferative and apoptotic effect of antiestrogens (HodgesGallagher et al, 2008). However, data regarding the association of ERb expression with clinical pathological parameters and antiestrogen responsiveness are still mixed (Speirs et al, 1999;O'Neill et al, 2004;Murphy and Watson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The region of the mRNA targeted by primers may also influence which variants are detected. Several investigators have reported that ERβ mRNA levels often do not correlate with ERβ protein in breast tumor tissues [80][81][82][83][84], and confusion with ERβ status in tumors may result from this method. If fact, in one report only 54% of ERβ mRNA-positive tumors correlated with ERβ protein levels [84].…”
Section: Coexpression Of Erβ With Erα and Other Potential Markers In mentioning
confidence: 99%
“…Both antibody types have been used; however, sample preparation and integrity as well as specific staining protocols may influence outcomes [79]. With variation in the choice of ERβ antibody and tissue fixation protocols, there is not yet firm agreement on the appropriate cutoff value for determining ERβ positivity [78,82].…”
Section: Coexpression Of Erβ With Erα and Other Potential Markers In mentioning
confidence: 99%
See 2 more Smart Citations